Evaluation of the relationship between the quality of panoramic radiographs and BMI (body mass index) of patients referring to a dental clinic in Isfahan in 2011 - Ehsan Hekmatian; Mohammad Shah Abuei; Mahsayeh Lashkari Zadeh Bami (Isfahan University of Medical Sciences, 2012)
AbstractIntroduction: The quality of panoramic radiographs has a great role in the diagnosis of lesions. The aim of the present study was to evaluate the effect of BMI and the type of the radiographic cassette on the diagnostic quality of panoramic images through evaluation of maxillary sinus periphery, mandibular cortex, tooth enamel and tooth fillings. Materials and methods: In this cross-sectional study, 400 patients with an age range of 2-70 years, who required panoramic radiographs, were selected .Type of the cassette used and patients' weights, heights and ages were recorded before radiography. After processing the images, each anatomical landmark was scored on a 3-point scale. Total quality for each image was defined as the average of these scores for selected landmarks. The overall density of each image (i.e. the overall quality) was also scored. Data were analyzed by Spearman's correlation coefficient, Mann-Whitney test, t-test and regression test (α=0.05).Results: Spearman's correlation coefficient revealed a significant correlation between BMI and resolution of the periphery of maxillary sinus and the overall image density (p value < 0.0001). No correlation was found between BMI and resolution of mandibular cortex (p value = 0.7) and tooth crown enamel and fillings (p value = 0.2). Cassette type had no effect on image quality. Conclusion: The results indicated cassette type has no effect on image quality provided other exposure factors are properly chosen. Furthermore, an increase in BMI has no effect on resolution of anatomic landmarks provided that other exposure factors are properly chosen, although it increases image density. It appears panoramic radiographic technique is a useful diagnostic tool, especially for adults. Key words: Body mass index, Image quality, Panoramic, Radiography.